A 1% treadmill grade most accurately reflects the energetic cost of outdoor running - Jones, A. M.; Doust, J. H. (Journal of Sports Sciences, 1996)
When running indoors on a treadmill, the lack of air resistance results in a lower energy cost compared with running outdoors at the same velocity. A slight incline of the treadmill gradient can be used to increase the energy cost in compensation. The aim of this study was to determine the treadmill gradient that most accurately reflects the energy cost of outdoor running. Nine trained male runners, thoroughly habituated to treadmill running, ran for 6 min at six different velocities (2.92, 3.33, 3.75, 4.17, 4.58 and 5.0 m s-1) with 6 min recovery between runs. This routine was repeated six times, five times on a treadmill set at different grades (0%, 0%, 1%, 2%, 3%) and once outdoors along a level road. Duplicate collections of expired air were taken during the final 2 min of each run to determine oxygen consumption. The repeatability of the methodology was confirmed by high correlations (r = 0.99) and non-significant differences between the duplicate expired air collections and between the repeated runs at 0% grade. The relationship between oxygen uptake (VO2) and velocity for each grade was highly linear (r > 0.99). At the two lowest velocities, VO2 during road running was not significantly different from treadmill running at 0% or 1% grade, but was significantly less than 2% and 3% grade. For 3.75 m s-1, the VO2 during road running was significantly different from treadmill running at 0%, 2% and 3% grades but not from 1% grade. For 4.17 and 4.58 m s-1, the VO2 during road running was not significantly different from that at 1% or 2% grade but was significantly greater than 0% grade and significantly less than 3% grade. At 5.0 m s-1, the VO2 for road running fell between the VO2 value for 1% and 2% grade treadmill running but was not significantly different from any of the treadmill grade conditions. This study demonstrates equality of the energetic cost of treadmill and outdoor running with the use of a 1% treadmill grade over a duration of approximately 5 min and at velocities between 2.92 and 5.0 m s-1.